The Influence of Product Quality on Customer Satisfaction in Asik Creative Gresik, East Java - Arimawasti, Indi; Suwaidi, Rahman Amrullah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the effect of product quality on customer satisfaction in Asik Creative, Gresik, East Java. This research method uses quantitative research with the independent variable being product quality and the dependent variable being customer satisfaction. In this research, data was collected using questionnaires. The population in this research are clients of Asik Creative. The number of samples taken was 50 respondents. This research uses the SEM PLS method to conduct quantitative analysis. Each indicator is tested for validity and reliability, then continued with the coefficient of determination test, and continued with hypothesis testing using the t-test. This research produces a statement that product quality dimensions such as performance, features, reliability, conformity to specifications, durability, aesthetics, and impression of quality have a significant influence on customer satisfaction.